2013
DOI: 10.1111/pai.12036
|View full text |Cite
|
Sign up to set email alerts
|

Rupatadine oral solution in children with persistent allergic rhinitis: A randomized, double‐blind, placebo‐controlled study

Abstract: Rupatadine oral solution (1 mg/ml) was significantly more effective than placebo in reducing nasal symptoms at 4 and 6 wk and was well tolerated overall. This is the first large clinical report on the efficacy of an H1 receptor antagonist in children with PER in both symptoms and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 26 publications
3
48
0
Order By: Relevance
“…The statistic for inter-rater agreement on study eligibility was 0.65. In six trials some data were not fully reported and could not be extracted from the manuscript 23,27,28,29,30,31 , thus requiring their acquisition from graphs by digitization, otherwise authors or manufacturers were contacted to obtain raw data.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The statistic for inter-rater agreement on study eligibility was 0.65. In six trials some data were not fully reported and could not be extracted from the manuscript 23,27,28,29,30,31 , thus requiring their acquisition from graphs by digitization, otherwise authors or manufacturers were contacted to obtain raw data.…”
Section: Study Selectionmentioning
confidence: 99%
“…Following the exclusion of documents not related to the topic (review, different outcomes, not placebo controlled, open design, not randomized studies, different disease from AR, pharmacokinetics studies), 17 studies were assessed in full text for potential eligibility [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] . Finally 10 DBPC RCTs satisfied the inclusion criteria and entered the qualitative and quantitative analysis [23][24][25][26][27][28][29][30][31][32] (Figure 1). The statistic for inter-rater agreement on study eligibility was 0.65.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The safety of rupatadine has been evaluated in randomized, double-blind, placebo-controlled studies in patients 12-65 years of age with chronic idi-opathic urticaria and in children 6-11 years of age with persistent allergic rhinitis [42][43][44].…”
Section: Rupatadine (C26h26cin3)mentioning
confidence: 99%